Fushiming Capsule Attenuates Diabetic Rat Retina Damage via Antioxidation and Anti-Inflammation. (18th July 2019) - He, Mengshan; Long, Pan; Guo, Lunfeng; Zhang, Mingke; Wang, Siwang; He, Hongling
Abstract : Aims . Diabetic retinopathy (DR) remains one of the leading causes of acquired blindness. Fushiming capsule (FSM), a compound traditional Chinese medicine, is clinically used for DR treatment in China. The present study was to investigate the effect of FSM on retinal alterations, inflammatory response, and oxidative stress triggered by diabetes. Main Methods . Diabetic rat model was induced by 6-week high-fat and high-sugar diet combined with 35 mg/kg streptozotocin (STZ). 30 days after successful establishment of diabetic rat model, full field electroretinography (ffERG) and optical coherence tomography (OCT) were performed to detect retinal pathological alterations. Then, FSM was administered to diabetic rats at different dosages for 42-day treatment and diabetic rats treated with Calcium dobesilate (CaD) capsule served as the positive group. Retinal function and structure were observed, and retinal vascular endothelial growth factor- α (VEGF- α ), glial fibrillary acidic (GFAP), and vascular cell adhesion protein-1 (VCAM-1) expressions were measured both on mRNA and protein levels, and a series of blood metabolic indicators were also assessed. Key Findings . In DR rats, FSM (1.0 g/kg and 0.5 g/kg) treatment significantly restored retinal function (a higher amplitude of b-wave in dark-adaptation 3.0 and OPs2 wave) and prevented the decrease of retinal thickness including inner nuclear layer (INL), outer nuclear layer (ONL), and entire retina. Additionally, FSM dramatically decreased VEGF- α, GFAP, and VCAM-1 expressions in retinal tissues. Moreover, FSM notably improved serum antioxidative enzymes glutathione peroxidase, superoxide dismutase, and catalase activities, whereas it reduced serum advanced glycation end products, methane dicarboxylic aldehyde, nitric oxide, and total cholesterol and triglycerides levels. Significance . FSM could ameliorate diabetic rat retina damage possibly via inhibiting inflammation and improving antioxidation.